2013
DOI: 10.1038/srep01909
|View full text |Cite
|
Sign up to set email alerts
|

Digital optical phase conjugation for delivering two-dimensional images through turbid media

Abstract: Optical transmission through complex media such as biological tissue is fundamentally limited by multiple light scattering. Precise control of the optical wavefield potentially holds the key to advancing a broad range of light-based techniques and applications for imaging or optical delivery. We present a simple and robust digital optical phase conjugation (DOPC) implementation for suppressing multiple light scattering. Utilizing wavefront shaping via a spatial light modulator (SLM), we demonstrate its turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
81
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 137 publications
(83 citation statements)
references
References 26 publications
0
81
0
1
Order By: Relevance
“…Second, to ensure well-sampling speckle grains by magnifying the speckle size, a lens with an iris [44] (Fig. 1e), or two high-magnification objective lenses [23,25,29] (Fig. 1f), are usually employed, and the PCM is always placed far from the rear surface of the scattering medium.…”
mentioning
confidence: 99%
“…Second, to ensure well-sampling speckle grains by magnifying the speckle size, a lens with an iris [44] (Fig. 1e), or two high-magnification objective lenses [23,25,29] (Fig. 1f), are usually employed, and the PCM is always placed far from the rear surface of the scattering medium.…”
mentioning
confidence: 99%
“…This property has allowed fascinating demonstrations such as the removal of inhomogeneity in the generation of photon echoes [4] or perfect absorption which is the opposite of lasing [5]. In imaging, multiple scattering and the principle of time reversal have been capitalized in reconstructing the incident field prior to multiple scattering [6][7][8]. In the microwave region, it has also been shown that scattering materials placed in the near field of a target object can scatter the near fields into propagating farfield components [9,10].…”
mentioning
confidence: 99%
“…23 Alternatively, phase conjugation methods have also been widely utilized for focusing through biological tissues. [24][25][26][27] This phase conjugation approach utilizes the general reciprocity of the turbid media which guarantees that every light path is bilateral. Since the optical path would not be changed under time reversal, identical scattering information can be obtained from reversed pathways.…”
Section: Focusing Through Biological Tissuesmentioning
confidence: 99%